Pronouncing Shakespeare's words : a guide from A to Zounds - Coye, Dale F. (Westport, Conn. : Greenwood Press, 1998)
A pronunciation guide to some of the difficult words in the plays and poems of Shakespeare; listed by act, scene, and line in the order they appear in each work.
Includes bibliographical references (p. [679]-682) and indexes.
Booklist.
Library Journal.
Wilson's Senior High School.
Adult.
Adult
Keywords: Shakespeare, William, -- 1564-1616 -- Language; Shakespeare, William, -- 1564-1616 -- Language; English language -- Early modern, 1500-1700 -- Pronunciation -- Dictionaries; English language -- Pronunciation